What drives and constrains effective leadership in tackling child undernutrition?: Findings from Bangladesh, Ethiopia, India and Kenya - Nisbett, Nicholas; Wach, Elise; Haddad, Lawrence James; El Arifeen, Shams (Elsevier, 2015)
Strong leadership has been highlighted as a common element of success within countries that have made rapid progress in tackling child and maternal undernutrition. Yet little is known of what contributes to nutrition leaders' success or lack of it in particular policy environments. This study of 89 individuals identified as influential within child and maternal undernutrition policy and programming in Bangladesh, Ethiopia, Kenya and India sheds light on why particular individuals have been effective in contributing towards positive changes in nutrition policy, and how they operate in the wider policy/political sphere. We employ a framework working outwards from individual capabilities, knowledge and motivations, through to wider political economy considerations and the narratives and knowledge structuring individual capacity. We argue that only by locating individuals within this wider political economy can we begin to appreciate the range of strategies and avenues for influence (or constraints to that influence) that individual leaders employ and encounter.